Treatment dependent sodium-rich Prussian blue as a cathode material for sodium-ion batteries. Issue 25 (14th June 2022) - Wang, Peiyuan; Li, Yonghao; Zhu, Denggui; Gong, Feilong; Fang, Shaoming; Zhang, Yonghui; Sun, Shumin
Abstract : Sodium ascorbate aqueous solution as the washing solution for the preparation of Prussian blue can inhibit the loss of Na + and the oxidation of Fe 2+, so as to achieve excellent electrochemical sodium storage performance. Abstract : In the preparation of Prussian blue analogs (PBAs), Na + loss and Fe 2+ oxidation take place when washing with water. Sodium-rich PBAs were prepared with sodium ascorbate aqueous solution as the washing solution, which can suppress the Na + loss and Fe 2+ oxidation. As the cathode of sodium-ion batteries, it exhibited excellent electrochemical performance.